Cultural Politics--Queer Reading - Sinfield, Alan (Book collections on Project MUSE., 1994)
Was Shakespeare gay? Is The Merchant of Venice anti-Semitic? How does mainstream reading differ from that of subcultural groups? In this lively and readable book, Alan Sinfield challenges the assumptions of English literature and investigates the principles and practices that may inform lesbian and gay reading.